Ministry of Trade and Industry Decree No. 1035 For The Year 2010 On Ceasing the Exportation of the White Sugar = وزارة التجارة والصناعة قرار رقم 1035 لسنة 2010 فى شأن وقف تصدير السكر الأبيض - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.